Extensor digitorum brevis muscle flap and its donor site morbidity: A case report with review of literature - Marra, Caterina; Pinelli, Massimo; Taccioli, Filippo; Benivegna, Dario; De Santis, Giorgio (Acta Biomedica Atenei Parmensis, 2024)
Introduction: The dorsum of the foot is one the most challenging areas to be reconstructed, because of the terminal vascularization, the thin skin, and the limited muscle mass. Muscle flaps are the gold standard for treating exposed bones, osteomyelitis, and soft tissue infections. The extensor digitorum brevis digitorum (EDB) flap is a reliable, versatile, and practical locoregional solution for covering small to medium-sized defects in the ankle region. However, its use remains highly controversial because of significant donor-site morbidity. Case report: We show a case of an Italian 59-year-old male with a right medial malleolus exposure following a blunt-sprain trauma and covered with an EBD flap. While the flap always remained vital, the patient developed donor-site skin necrosis, requiring surgical debridement with extensor tendons exposure.  A dermal substitute (Integra ®) was positioned over the extensor tendons, but, due to an infection, antibiotic therapy, dressings and Negative Pressure Wound Therapy (NPWT) were necessary. At the end, a dermal-epidermal graft was used to cover the donor site and the muscle flap. Conclusion: As this case report suggests, the EDB flap is a practical option, but its donor-site morbidity is a non-negligible problem, as our literature review underlined. To reduce the complication rate, careful patient selection and pre-operative planning must be performed.